Dampak pola asuh pada pendidikan anak: Pola asuh dan pendidikan - Faizah, Zahrotul Aning Nur (Maliki Interdisciplinary Journal, 2024)
Successful parents in educating children still need to learn how to provide the best care for children. Through counseling related to how to care for children properly and correctly, hoping to help the problem of wrong parenting from parents caused by lack of knowledge and skills in their care, Where from the counseling will have a positive influence on improving parenting. Because with the best parenting, it will also have an impact on his education. So it can be concluded that there is a significant relationship between parenting and children’s education in the future.